2021
DOI: 10.3390/cells10071685
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Neutrophil to Lymphocyte Ratio (NLR) in Luminal Breast Cancer: A Retrospective Analysis in the Neoadjuvant Setting

Abstract: The neutrophil to lymphocyte ratio (NLR) is a promising predictive and prognostic factor in breast cancer. We investigated its ability to predict disease-free survival (DFS) and overall survival (OS) in patients with luminal A- or luminal B-HER2-negative breast cancer who received neoadjuvant chemotherapy (NACT). Pre-treatment complete blood cell counts from 168 consecutive patients with luminal breast cancer were evaluated to assess NLR. The study population was stratified into NLRlow or NLRhigh according to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…NLR is one of the most commonly evaluated immunocyte ratio in breast cancer, and has often been shown to significantly associate with OS, DFS or pCR [ 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, few studies have evaluated applying more than one single immunocyte ratio in their cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR is one of the most commonly evaluated immunocyte ratio in breast cancer, and has often been shown to significantly associate with OS, DFS or pCR [ 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, few studies have evaluated applying more than one single immunocyte ratio in their cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) has emerged as a clinically-relevant measure of immune function in tumours, including breast cancer [ 8 , 9 , 10 , 11 ]. Ratios of peripheral blood cells have been correlated with clinically relevant outcomes, such as disease-free survival (DFS) and overall survival (OS) in breast cancer [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high NLR is generally associated with poor prognosis, as neutrophils have the potential to inhibit anti-tumor immunity by secreting a variety of inflammatory mediators and suppressing the cytotoxic activity of T cells [ 11 , 12 ]. However, the correlation between the biomarker and patient survival is much less consolidated in the neoadjuvant setting [ 13 , 14 , 15 ]. Many studies emphasize that a low pre-treatment NLR is associated with an increased pathologic complete response (pCR) rate [ 16 ], but this is particularly related to the tumor molecular subtype, and its correlation with long-term outcomes is still debated [ 8 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 300 reports in PubMed and several systematic reviews and meta-analyses concern "neutrophil lymphocyte ratio, and breast cancer" [3][4][5][6]. More recent studies have reported a poorer prognosis and shorter survival times for breast cancer patients with higher NLRs [7][8][9][10][11]. The majority of these studies indicated that an NLR greater than the cutoff value of ~ 3 was associated with worse overall survival (OS) (hazard ratio (HR) 2.56, 95% confidence intervals CI = 1.96-3.35; P < 0.001) and disease-free survival (DFS) (HR 1.74, 95% CI = 1.47-2.07; P < 0.001), with a greater prognostic value for DFS in ER-negative and HER2-negative breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%